Artikel Perancangan Sistem Pengadaan Distribusi Alat Kebersihan di Kantor Walikota Palembang menggunakan Metode Spiral - Muhammad Fakhri Asshofi; Muhammad Faiz Athallah; Rewina Rakha Phelia Paramesti; Zulfah Shabirah; Syawaluddin Boy Rambe Al-Ayyubi; Gading Putra Abdi; Miftahul Falah (Jurnal Media Informatika, 2026)
The management of procurement and distribution of cleaning equipment in government institutions plays an important role in supporting daily operational activities. However, the manual process currently implemented at the Palembang Mayor’s Office has caused several problems, such as delays in submitting requests, stock recording errors, document loss, and difficulties in monitoring distribution in real time. This study aims to design and develop a web-based Information System for the Procurement and Distribution of Cleaning Equipment using the Spiral Method. The Spiral Method was selected due to its iterative nature, adaptability to changing requirements, and its emphasis on risk analysis at each development stage. The research stages include problem identification, data collection through observation and interviews, system design using UML, implementation using PHP and MySQL, and system testing using the Black Box Testing method. The results indicate that the developed system successfully integrates the processes of request submission, verification, approval, distribution, and reporting into a single integrated platform. System testing shows a functional success rate of 100%, indicating that all features operate according to user requirements. Therefore, the system is expected to improve efficiency, transparency, and accountability in managing the procurement and distribution of cleaning equipment at the Palembang Mayor’s Office.